Tingkat Pelaksanaan Problem-Based Learning di Fakultas Kedokteran Universitas Gadjah Mada Berdasarkan Pembelajaran Konstruktif, Mandiri, Kolaboratif, dan Kontekstual - Banu Aji Dibyasakti; Gandes Retno Rahayu; Yoyo Suhoyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Problem-based Learning (PBL) is a new strategy on a learning system. There are four basic theories regarding PBL such as constructive, self-directed, collaborative, and contextual learning. The success of the implementation of PBL in one institution can be measured by the implementation of its four basic theories. Faculty of Medicine UGM (FM UGM) has been implementing PBL as their curriculum since 2002, however there have not been any conducted research that measure the implementation of PBL in FM UGM towards its 4 (four) basic theories. The objectives of this study are to validate instrumen developed by Romauli et al8 that can measure the implementation level of PBL towards its 4 basic theories, to measure the implementation level of PBL in FM UGM towards its 4 basic theories, and to compare the implementation level of PBL based on students’ academic level and regular/international program.Method: This research used quantitative non-experimental research with cross-sectional design. 321 students from 2nd (2008) and 3rd (2007) students’batch regular and international program filled the questionnaire developed by Romauli et al (2009) which had been reliable (Alpha Cronbach) and validated (Pearson Moment Product) twice previously. The data were analyzed using mean analysis to measure the implementation level of PBL towards its four basic theories. This research also compared the implementation level of PBL based on students’ academic level and regular/international by using Independent Sample t-test.Results: Instrument developed by Romauli et al8 had high validity and reliability level (á=0,01 and r=0,931). The implementation level of PBL in FM UGM towards constructive, self-directed, collaborative, and contextual learning were in moderate level (1,72±0,28;min 0 & max 3). There were not any significant differences of the implementation level of PBL among 2007 & 2008 batch (p>0,05). There were any significant differences of the implementation level of PBL among regular & international students regarding constructive & contextual learning (p<0,05), however there were not any significant differences for self-directed & collaborative learning, (p>0,05).Conclusion: Instrument developed by Romauli et al (2009) had high validity and reliability. The implementation level of PBL were in moderate level. There were not any significant differences of the implementation level of PBL among two different students’ batch. There were any significant differences of the implementation level of PBL among reg